Peningkatan Keterampilan Penggunaan APAR ber-SNI dan Alat Pemadam Tradisional Sebagai Mitigasi Bencana Kebakaran Pada Pemukiman Padat Penduduk di Desa Sipatuo - Indrayani, Devi Lilis; Asmiranti, Asmiranti; Zulfa, Nurul Nadifa Maharani; Mawardi, Alifah Dzakiyah; Pardiansah, Pardiansah; Mappatunru, Andi Alung; Mustaainun, Mustaainun; Rizaluddin, Akhmad Akbar; Permana, Imam (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Fire disasters are disasters that have a high potential that often occur in Indonesia. One of the fire disasters that often occurs is fires caused by LPG fuel. Public understanding and awareness of fire safety can be categorized as low. This can be seen from fire incidents caused by negligence in using LPG cylinders. Intervention is a method used in practice in the field in the fields of social work and social welfare. In this community service activity, KKN students provided counseling and training on the use of APAR and traditional tools to prevent fires in Sipatuo Village, Patampanua District, Pinrang Regency. In the counseling, ways to prevent the emergence of fire hazards were carried out, starting from the correct placement of LPG gas cylinders and damage to the regulator. The results of this outreach activity provide residents with an understanding of the components in gas stoves that can cause fire hazards, residents can understand the function of gas regulators, gas hoses and gas cylinder layouts in preventing fire hazards and know how to use APARs and traditional fire prevention tools.